The future Malaysian dental workforce: System Dynamic (SD) modelling - Che Musa, Muhd Firdaus; Bernabe, Eduardo; Gallagher, Jennifer E. (2017)
Objective: To model the dental workforce in Malaysia, a middle-income country where dental workforce production has rapidly expanded over the past 10 years. Methods: A systems dynamic (SD) model was developed using commercial software (Vensim) to examine the need and demand for, and supply of, dental care from 2010 till 2040. Sub-models related to ‘population need and demand’; and, ‘workforce supply’, drawing on the findings of student surveys and interviews of key stakeholders in Malaysia. First, the need/demand sub-model involved integrating population demographic and oral health trends with levels of demand for care (patients’ preference on sector and type of care) by population age-band. Second, the workforce supply sub-model involved dentists (generalists, specialists) and therapists by sector (public, private) and working pattern (full- and part-time), both locally and internationally qualified. Sub-models were then run and integrated to explore the relationship between the models including potential over- or under-supply of the clinical hours, converted to clinical workforce numbers. This SD model was validated structurally and behaviourally. Results: The findings highlight the current gap between population need/demand and workforce capacity, which represents an undersupply that is expected to close over time and result in a potential oversupply emerging from 2035 onwards. The need/demand for both primary and secondary dental care is expected to increase by over 130% and 51% from the year 2010 to almost 38.8 million and 11.2 million hours respectively by 2040, and vary by age-band. Supply projections indicate that on the current trajectory, there will be almost a tenfold increase in the volume of dentists and doubling of therapists by 2040. Conclusion: Should current rates of workforce capacity building to address workforce shortages continue, there the findings suggest that by 2040, there is likely to be an oversupply of both dentists and therapists.